Multi‐omics provides new insights into the domestication and improvement of dark jute (Corchorus olitorius). (8th October 2022) - Yang, Zemao; Tian, Shilin; Li, Xiangkong; Dai, Zhigang; Yan, An; Chen, Zhong; Chen, Jiquan; Tang, Qing; Cheng, Chaohua; Xu, Ying; Deng, Canhui; Liu, Chan; et al.
SUMMARY: Jute ( Corchorus sp.) is the most important bast fiber crop worldwide; however, the mechanisms underlying domestication and improvement remain largely unknown. We performed multi‐omics analysis by integrating de novo sequencing, resequencing, and transcriptomic and epigenetic sequencing to clarify the domestication and improvement of dark jute Corchorus olitorius . We demonstrated that dark jute underwent early domestication and a relatively moderate genetic bottleneck during improvement breeding. A genome‐wide association study of 11 important agronomic traits identified abundant candidate loci. We characterized the selective sweeps in the two breeding stages of jute, prominently, soil salinity differences played an important role in environmental adaptation during domestication, and the strongly selected genes for improvement had an increased frequency of favorable haplotypes. Furthermore, we speculated that an encoding auxin/indole‐3‐acetic acid protein COS07g_00652 could enhance the flexibility and strength of the stem to improve fiber yield. Our study not only provides valuable genetic resources for future fiber breeding in jute, but also is of great significance for reviewing the genetic basis of early crop breeding. Significance Statement: We performed multi‐omics analysis by integrating de novo sequencing, resequencing, and transcriptomic and epigenetic sequencing to clarify the domestication and improvement of dark jute Corchorus olitorius . Our study not only provides valuable genetic resources for future fiber breeding in jute, but also is of great significance for reviewing the genetic basis of early crop breeding.